IMPACT OF EMPLOYEE ENGAGEMENT AND MOTIVATION ON EMPLOYEE PERFORMANCE IN PT INDONESIA MOROWALI INDUSTRIAL PARK - Prasadjaningsih, MC. Oetami; Alexandra, Marina (Dinasti Publisher, 2022)
Human Resources (HR) is the most valuable asset that company could ask for. Every employee will give their own benefit to company/organization when they achieved their target that set by the company. Company should try every way to make employee works as productive as possible to earn benefit. The purpose of this research is to analyze the impact of employee engagement and motivation on employee performance in PT Indonesia Morowali Industrial Park. Author using quantitative research which is a research method based on the philosophy of positivism, used to examine certain populations or samples. The analytical tool used is multiple linear regression with a significance level of five percent. The results of this study indicate that employee engagement and motivation have a positive and significant effect on employee performance.